Problems of Functional Performance and Space Gradient Organization in the Sidewalk of the Residential Street - Sanjary, Hasan Abdulrazzaq Al; Ahmad, Hatem Kasim (Sulaimani Journal for Engineering Sciences, 2017)
Sidewalk space forms one of the key elements in the residential street which is appeared with planning transitions in urban neighborhoods in Iraq over the past century. Despite the importance of this space as a zone for a range of functional activities that are supposed to achieve within space graduation ensures regulation of the relationship between house resident and road user, but the reality of the housing districts case presents a lot of problems that accompanied the design and furnishing of this space so as to create a number of obvious drawbacks in the effectiveness of its use. This research aims and through the evaluation of realistic design for local environment of housing in the city of Mosul to extract the most negative aspects of the functional performance of residential street pavement, their causes and down to extract the necessary indicators that can contribute to more effective performance of this space and reinforce its value as a functional and regulatory privacy zone within the housing environment.
Keywords: Residential street; Sidewalk; Functional performance; Urban housing; Residential neighborhood